Antes rir do que chorar: análise das relações familiares e afetivas em A Grande Família - Albeche, Daysi Lange (Universidade do Vale do Rio do Sinos, 2008)
The object of the analysis of this paper is the sitcom A grande família, from Globo Network Television, RGT, seeking to describe the structures that cast the program, identifying the themes presented and the behaviour models built, observing the contruction of the character’s profile and the attitude proposals that are offered to the televiewers. The case study, to identify the proposal of the program interaction and it’s logics of working was organized in two parts. In the first, we made a descriptive observation of the regularity of the program to capture its general structure, in the formal aspects: vignettes, episodes’ tittles, sceneries, patterns and the thematics approached; to do so, it was observed 106 episodes. For the second part ten episodes were selected analyzing the profiles of the characters and the sequences and the thematic approached. This second part made it possible to identify a group of stereotypes related to the different social interactions from the family/private scope that, treated i
Keywords: construção do leitor; endereçamento; sistema de resposta; sitcom; vida privada; humor; address; answer system; building of the reader; private life; humour; Ciências Sociais Aplicadas